Laser-induced radiation microbeam technology and simultaneous real-time fluorescence imaging in live cells. - Botchway, S; Reynolds, P; Parker, A; O'Neill, P (2012)
The use of nano- and microbeam techniques to induce and identify subcellular localized energy deposition within a region of a living cell provides a means to investigate the effects of low radiation doses. Particularly within the nucleus where the propagation and processing of deoxyribonucleic acid (DNA) damage (and repair) in both targeted and nontargeted cells, the latter being able to study cell-cell (bystander) effects. We have pioneered a near infrared (NIR) femtosecond laser microbeam to mimic ionizing radiation through multiphoton absorption within a 3D femtoliter volume of a highly focused Gaussian laser beam. The novel optical microbeam mimics both complex ionizing and UV-radiation-type cell damage including double strand breaks (DSBs). Using the microbeam technology, we have been able to investigate the formation of DNA DSB and subsequent recruitment of repair proteins to the submicrometer size site of damage introduced in viable cells. The use of a phosphorylated H2AX (γ-H2AX a marker for DSBs, visualized by immunofluorescent staining) and real-time imaging of fluorescently labeling proteins, the dynamics of recruitment of repair proteins in viable mammalian cells can be observed. Here we show the recruitment of ATM, p53 binding protein 1 (53BP1), and RAD51, an integral protein of the homologous recombination process in the DNA repair pathway and Ku-80-GFP involved in the nonhomologous end joining (NHEJ) pathway as exemplar repair process to show differences in the repair kinetics of DNA DSBs. The laser NIR multiphoton microbeam technology shows persistent DSBs at later times post laser irradiation which are indicative of DSBs arising at replication presumably from UV photoproducts or clustered damage containing single strand breaks (SSBs) that are also observed. Effects of the cell cycle may also be investigated in real time. Postirradiation and fixed cells studies show that in G1 cells a fraction of multiphoton laser-induced DSBs is persistent for >6h in addition to those induced at replication demonstrating the broad range of timescales taken to repair DNA damage.